Short proof of the fundamental theorem of algebra - Novikas, Aivaras; Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2025)
High school students may be introduced not only to important mathematical statements, such as the fundamental theorem of algebra, but also to their proofs. This famous theorem has various proofs, and its proofs have various modifications. The article discusses one such proof that is accessible to students.
Keywords: real polynomials; fundamental theorem of algebra; proof in school mathematics